Strengthening Brand Knowledge through Brand Orientation and Brand Involvement - Rafidah Salma Mardhiyah; Nurul Azizah (Future Science)
In the era of global competition, an organization is required to develop its existence. One effort to develop the existence of the organization is to strengthen the brand so that the loyalty and satisfaction of customers or users increases. Of course, this brand will become a distinctive feature in the organization. Brand knowledge is the first step in strengthening the organization's brand, especially for internal actors. As the theoretical foundation in the current research is internal branding, which consists of three variables, namely: Brand Orientation, brand involvement, and brand knowledge. The study sampled in this study was 285 employees at UPN